2015
DOI: 10.1002/hep.27710
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological cohort study of liver pathology in 301 patients with human immunodeficiency virus/acquired immune deficiency syndrome

Abstract: Liver disease complicates human immunodeficiency virus (HIV)/acquired immune deficiency syndrome; however, liver pathology data are limited, particularly from high HIV prevalence countries. We investigated the spectrum and clinicopathological correlates of liver pathology in a high HIV burden setting. In a single-center study, all HIV/acquired immune deficiency syndrome patients with complete clinical and demographic data who underwent liver biopsy were analyzed and clinicopathologically assessed by hepatologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…This finding suggests that through its suppressive effect on HIV replication, ART has the potential to prevent and/or reduce liver fibrosis in HIV-positive patients. Conversely, exposure to ART drug regimens with a known hepatic toxicity could also promote liver fibrosis [33,34]. The cross-sectional nature of our study design prevents any causal relation between ART use and the occurrence of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that through its suppressive effect on HIV replication, ART has the potential to prevent and/or reduce liver fibrosis in HIV-positive patients. Conversely, exposure to ART drug regimens with a known hepatic toxicity could also promote liver fibrosis [33,34]. The cross-sectional nature of our study design prevents any causal relation between ART use and the occurrence of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, NNRTIs are known for their potential to cause elevated liver enzymes, but have so far not been linked to fibrosis progression and remain commonly utilized (112). In addition, a recent study of liver biopsies in HIV-infected patients demonstrated drug induced liver injury due to antiretroviral therapy in a significant number of patients (113).…”
Section: Hiv-related Factors Influencing Liver Fibrosismentioning
confidence: 96%
“…21 Series HIV-HBV co-infection promotes an aggressive disease course of hepatitis B by the following mechanisms: increasing replication of the virus and rates of HBV reactivation; increasing risk of acute liver failure, chronicity of newly acquired HBV infections, and occult infection (characterised by absence of HBsAg and low viral replication; HBV DNA concentration <200 IU/mL); accelerating progression to fibrosis and cirrhosis, with hepatocellular carcinoma occurring at a younger age; and increasing the risk of ART hepatotoxicity. 14,15,17,18,[22][23][24][25][26][27][28][29] Liver-related mortality is twice as high for individuals who are co-infected with HIV-HBV as it is for those who are co-infected with HIV-HCV. Individuals with a CD4 cell count of less than 200 cells per mL have a risk of liver-related deaths that is 16•2 times higher than that of those with a CD4 count of more than 350 cells per mL.…”
Section: Effect Of Hivmentioning
confidence: 99%